British infantryman in the Far East, 1941-1945 - Jeffreys, Alan (Warrior, 2003)
This title focuses on the experience, tactics, training and weapons of the British soldier from the Fall of Malaya and Singapore until the Reconquest of Burma during World War II (1939-1945). It takes a close look at jungle warfare training in India and the ensuing action in Burma, tracing the development of tactics and doctrine: this formed the basis for the victories in the Arakan and the battles of Kohima and Imphal. The soldier's view of India, the entertainment available on leave, food rationing and other supplies such as cigarettes, the introduction of the forces newspaper SEAC, and the medical problems of malaria are all explored in detail.